Multibasillary Leprae Lepromatous Leprosy Type Relaps with Erythema Nodosum Leprosum Reaction: Establishing the Diagnosis - Ria Margiana (Journal of Global Pharma Technology, 2016)
Introduction: Leprosy or Morbus Hansen is a disease caused by infection with Mycobacterium Leprae with manifestations in the skin and peripheral nerves that can cause neuropathy or disability. The case of relapse in leprosy is a condition in which patients who have successfully completed the MDT (multi drug therapy) program with complete and appropriate but there are new symptoms of the disease either during the monitoring period or after. ENL reactions can occur at any time, namely before, during and after MDT therapy. Case: A woman aged 43 years comes to Dermatovenereology clinic with complaints of red bumps accompanied by pain in the face and extremities. On physical examination fromt the facial, superior and inferior limbs appear multiple erythematous nodules with partial hyper pigmented, multiple, indistinct boundaries. Investigation in the form of an AFB test indicates the presence of IB + 3 and IM 0% which previously earned IB +1 IM 2.09%. Histopathological examination revealed an ENL reaction with a red acid-resistant bacillus. The patient is diagnosed with leprosy MB type LL RFT1, 5 years relapsed with ENL Discussion: Relapse or recurrence in leprosy can occur due to a variety of factors, one of which is due to the presence of persistent leprosy bacilli, Becx-Bleumink criteria can be used as a reference for diagnosing relapse that includes clinical features, BTA examination and histopathological features.Keywords: Erythema nodosum leprosum, Leprosy, Relapse.